Cavity-mediated thermal control of metal-to-insulator transition in 1T-TaS2 - Jarc, Giacomo; Mathengattil, Shahla Yasmin; Montanaro, Angela; Giusti, Francesca; Rigoni, Enrico Maria; Sergo, Rudi; Fassioli Olsen, Francesca; Winnerl, Stephan; Dal Zilio, Simone; Mihailovic, Dragan; Prelovšek, Peter; Eckstein, Martin; et al. (Nature, 2023)
Placing quantum materials into optical cavities provides a unique platform for controlling quantum cooperative properties of matter, by both weak and strong light–matter coupling1,2. Here we report experimental evidence of reversible cavity control of a metal-to-insulator phase transition in a correlated solid-state material. We embed the charge density wave material 1T-TaS2 into cryogenic tunable terahertz cavities3 and show that a switch between conductive and insulating behaviours, associated with a large change in the sample temperature, is obtained by mechanically tuning the distance between the cavity mirrors and their alignment. The large thermal modification observed is indicative of a Purcell-like scenario in which the spectral profile of the cavity modifies the energy exchange between the material and the external electromagnetic field. Our findings provide opportunities for controlling the thermodynamics and macroscopic transport properties of quantum materials by engineering their electromagnetic environment.
CRIS-Team Scopus Importer:2023-10-27

Manipulation of Charge Delocalization in a Bulk Heterojunction Material Using a Mid-Infrared Push Pulse - Montanaro, Angela; Park, Kyu Hyung; Fassioli Olsen, Francesca; Giusti, Francesca; Fausti, Daniele; Scholes, Gregory D. (Journal of Physical Chemistry C, 2023)
In organic bulk heterojunction materials, charge delocalization has been proposed to play a vital role in the generation of free carriers by effectively reducing the Coulomb attraction via an interfacial charge transfer exciton (CTX). Pump-push-probe (PPP) experiments produced evidence that the excess energy given by a push pulse enhances delocalization, thereby increasing photocurrent. However, previous studies have employed near-infrared push pulses in the range ∼0.4–0.6 eV, which is larger than the binding energy of a typical CTX. This raises the doubt that the push pulse may directly promote dissociation without involving delocalized states. Here, we perform PPP experiments with mid-infrared push pulses at energies that are well below the binding energy of a CTX state (0.12–0.25 eV). We identify three types of CTXs: delocalized, localized, and trapped. The excitation resides over multiple polymer chains in delocalized CTXs, while it is restricted to a single chain (albeit maintaining a degree of intrachain delocalization) in localized CTXs. Trapped CTXs are instead completely localized. The pump pulse generates a “hot” delocalized CTX, which promptly relaxes to a localized CTX and eventually to trapped states. We find that photo-exciting localized CTXs with push pulses resonant to the mid-infrared charge transfer absorption can promote delocalization and, in turn, contribute to the formation of long-lived charge separated states. On the other hand, we found that trapped CTXs are non-responsive to the push pulses. We hypothesize that delocalized states identified in prior studies are only accessible in systems where there is significant interchain electronic coupling or regioregularity that supports either inter- or intrachain polaron delocalization. This, in turn, emphasizes the importance of engineering the micromorphology and energetics of the donor–acceptor interface to exploit the full potential of a material for photovoltaic application
Keywords: Absorption; Charge transfer; Energy; Excitons; Polarons